Hak Veto Pada Perserikatan Bangsa-Bangsa Dan Dewan Keamanan Perserikatan Bangsa-Bangsa - Aurellia Nayla Putri Wijaya; Elyassin Firdaus; Rosaria Vani Kurniasari; Marsya Amalina Djatmiko; Sebastian Sitohang; Rani Pajrin (Pusat Riset dan Inovasi Nasional, 2024)
The veto right which is exclusively granted for the permanent members of the United Nations (UN) Security Council will always be controversial, especially for the international community. This journal discusses the study of the veto right based on the principles of International Law with a qualitative descriptive approach so as to achieve a systematic and factual picture and refers based on what is listed in the Legislation. Based on the existing analysis, the Veto Right is implicitly regulated in Article 27 paragraph (3) of the United Nations Charter which will be clearly seen in the article if the Veto Right is contrary to the original purpose of the establishment of the United Nations. This research will also further discuss the definition and history of the development of the veto right, the Security Council in general at the United Nations, as well as an analysis of the case of the use of the veto right.